Pengaruh Pemberian Penguatan Verbal Terhadap Motivasi Belajar Murid SD Inpres Paku Kabupaten Gowa - Ashar Ashar; Muhammad Nawir; Sulfiana Sulfiana; Nurul Asmila; Nadia Aghni Izzani A nisyar (Innovative: Journal Of Social Science Research, 2023)
This study aims to examine and test the effect of giving verbal reinforcement carried out by the teacher to students in the learning process on the learning motivation of SD Inpres Paku Elementary School students, Gowa Regency. The type of research used in this research is a quantitative approach using the ex post facto method with a sample of 35 respondents. The data collection method used is observation and a questionnaire/questionnaire. Data analysis techniques in this study used simple linear regression analysis with validity test, reliability test, classical assumption test, hypothetical test, and coefficient of determination test. The results of the study stated that the value of the correlation coefficient denoted by R was 0.779, while the percentage (%) R Square (R2) was 0.530, which means that the effect of variable X (providing verbal reinforcement) on variable Y (student learning motivation) was 53.0%. the rest is influenced by other variables outside those studied. Based on the results of this research, it shows that there is a positive and significant effect of providing verbal reinforcement on the learning motivation of fourth grade students at SD Inpres Paku, Gowa Regency.